Carbon Dots Enabling Parts-Per-Billion Sensitive and Ultraselective Photoluminescence Lifetime-Based Sensing of Inorganic Mercury - Zdražil, Lukáš; Panáček, David; Šedajová, Veronika; Baďura, Zdeněk; Langer, Michal; Medveď, Miroslav; Paloncýová, Markéta; Scheibe, Magdalena; Kalytchuk, Sergii; Zoppellaro, Giorgio; Kment, Štěpán; Cadranel, Alejandro; et al. (Advanced Optical Materials, 2023)
One of the UN Sustainable Development Goals is to ensure universal access to clean drinking water. Among the various types of water contaminants, mercury (Hg) is considered to be one of the most dangerous ones. It is mostly its immense toxicity and vast environmental impact that stand out. To tackle the issue of monitoring water quality, a nanosensor based on carbon dots (CDs) is developed, whose surface is functionalized with carboxylic groups. CDs show Hg2+ concentration-dependent photoluminescence (PL) lifetimes along with an ultrahigh sensitivity and selectivity. The selectivity of PL quenching by Hg2+ is rationalized by performing light-induced electron paramagnetic resonance (LEPR) spectroscopy showing significant perturbation of the CD photoexcited state upon Hg2+ binding. The experimental findings are supported by time-dependent density functional theory (TD-DFT) calculations. These unveiled the emergence of a low-lying charge transfer state involving a vacant 6s orbital of Hg2+ stabilized by relativistic effects.
CRIS-Team Scopus Importer:2023-07-21
Keywords: carbon dots; colloidal nanomaterials; mercury sensing; time-resolved photoluminescence